Comparison of Morphometric Measurements of Traditional Posterior Cervical Screw and Paravertebral Foramen Screw in Chinese Population. Issue 7 (1st April 2021) - Chen, Xi; Yang, Qing; Kalisi, Kupu Uluakimata Mei Muli; Yuan, Suomao; Tian, Yonghao; Liu, Xinyu
Abstract : Study Design: A morphometric measurement study. Objective: To measure the length and angle parameters of the screw paths of pedicle screws (PS), lateral mass screws (LMS), and paravertebral foramen screws (PVFS) of subaxial cervical spine in Chinese population. Summary of Background Data: Aramomi proposed a novel internal fixation technology, named PVFS, as an alternative to LMS and PS for subaxial cervical vertebrae (C3-C7). Methods: This study measured the length and medial angles of screw paths on the three-dimensional reconstruction model of cervical computerized tomography data of 50 patients (25 men and 25 women) in our hospital from January 2018 to June 2018. Results: In general, the optimum length and medial angle of the PVFS in Chinese population were 10.65 mm and 21.12° at C3; 10.12 mm, 22.62° at C4; 9.82 mm, 23.66° at C5; 9.19 mm, 24.13° at C6; and 9.10 mm, 27.54° at C7. The optimum axial length and medial angle of PS in Chinese population were 30.94 mm, 33.92° at C3; 30.50 mm, 34.95° at C4; 31.92 mm, 33.42° at C5; 30.50 mm, 31.94° at C6; and 29.87 mm, 31.01° at C7. The optimum lengths of LMS paths in Chinese population were C3, 14.84 mm; C4, 15.33 mm; C5, 15.44 mm; C6, 14.74 mm; and C7, 14.06 mm. Conclusion: Although the length of PVFS is limited, it still can be used as an effective substitute for LMS and PS. The PVFS does not have the risk of directly injuring the vertebral artery, its safety angle of insertion is larger than that in PS, and it has higher surgical safety. Level of Evidence: 3 Abstract : This study measured the length and angle parameters of screw paths of cervical paravertebral foramen screws, pedicle screws, and lateral mass screws in reconstructed computerized tomography images. We measured that the length of paravertebral foramen screw was limited, its safety angle of insertion was larger than that in pedicle screw.